Entrepreneurial Risk Management of Buddhist Entrepreneurs - Mahadewi, Lufina; Surachman, Surachman; Hadiwidjojo, Djumilah; Indrawati, Nur Khusniyah (International Journal of Business Studies, 2022)
This study aims to explore and understand the context of the behavior and perceptions of Buddhist entrepreneurs in the application of risk management in entrepreneurial activities. This study reveals the implementation of Buddhist values ​​in the framework of entrepreneurial risk management. This study is set in the setting of Buddhist entrepreneurs in the city of Bekasi, West Java, through a phenomenological qualitative research approach. This study reveals that risk management is a process of reducing inefficiencies that arise from the causal relationship of the actions of Buddhist entrepreneurs in the perspective of Buddhism, Truth in Dhamma. The values ​​of Buddha's teachings are the background for the risk management process which is characterized by an entrepreneurial spirit and character based on Buddhism. This implementation provides a form of motivation in an effort to eliminate risk in an attempt to create value from entrepreneurial activities for the beatitude of oneself and others by having an awareness that is focused on spiritual beatitude. Buddhist values ​​color the formation of an entrepreneurial culture which is reflected in the practices of Buddhist entrepreneurial risk management. The findings of this study provide developments on stakeholder theory on the fulfillment of financial and social performance to stakeholders and its relevance to the fulfillment of spiritual aspects. This study provides the development of stakeholder theory on the interaction between stakeholder attributes and the essential meaning of entrepreneurship in economic, social and spiritual contexts. This study reveals an integrated theoretical model of Buddhist value-based entrepreneurial risk management practices that not only raises the spectrum of traditional risk management, but reflects the value of Buddhism in entrepreneurial activities in fulfilling the goals of Buddhist entrepreneurs in the form of holistic adherence to Buddhist values ​​in personal and business life. Keywords: Entrepreneurial Risk Management, Risk Process, Buddhist Values